2019
DOI: 10.7127/rbai.v12n7001016
|View full text |Cite
|
Sign up to set email alerts
|

Atributos Químicos Do Solo Em Área Cultivada Com Milho Sob Irrigação Com Água Salina

Abstract: RESUMOO objetivo deste estudo foi avaliar o impacto do uso da água de diferentes salinidades sobre as alterações químicas de um Argissolo vermelho Amarelo cultivado com plantas de milho. O estudo foi conduzido em campo, no período de agosto a dezembro de 2017, na Fazenda experimental da Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB), Redenção-CE. O delineamento utilizado foi blocos ao acaso, com cinco níveis de salinidade da água de irrigação (1,0; 2,0; 3,0; 4,0 e 5,0 dS m -1 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…It is important to highlight that the presence of organic matter in all treatments with salinity promoted greater K + increments when compared to soil without organic matter; however, the availability of this ion was directly affected by the increase in salinity, given the antagonistic effects promoted by the increase in the concentrations of Na + , Ca 2+ , and Mg 2+ , which reduce the availability of K + by displacing it from the cation exchange complex (Martínez et al, 2022). Similar results were presented by Rodrigues et al (2018), who evaluated the chemical attributes of a soil irrigated with saline water and found reductions in potassium concentrations in the soil as a function of the increase in irrigation water salinity up to 5 dS m -1 .…”
Section: Resultssupporting
confidence: 82%
“…It is important to highlight that the presence of organic matter in all treatments with salinity promoted greater K + increments when compared to soil without organic matter; however, the availability of this ion was directly affected by the increase in salinity, given the antagonistic effects promoted by the increase in the concentrations of Na + , Ca 2+ , and Mg 2+ , which reduce the availability of K + by displacing it from the cation exchange complex (Martínez et al, 2022). Similar results were presented by Rodrigues et al (2018), who evaluated the chemical attributes of a soil irrigated with saline water and found reductions in potassium concentrations in the soil as a function of the increase in irrigation water salinity up to 5 dS m -1 .…”
Section: Resultssupporting
confidence: 82%
“…Similar results have been found by LESSA et al (2019), who have observed an increase in the salt level of the soil when using salt water to irrigate the sorghum crop. In addition, RODRIGUES et al (2018) have also reported similar results when verifying an increasing linear response of the electrical conductivity of the soil with the increase of the concentration of salts in the irrigation water.…”
Section: Discussionsupporting
confidence: 59%
“…In the semi-arid region of Brazil, due to adverse climatic conditions, characterized by having in most of the year high temperatures, high evapotranspiration rates and low rainfall, distributed irregularly in space and time, the use of irrigation becomes indispensable for the agricultural exploitation. However, due to the high demand for good quality water, together with the need to produce food, the use of lower quality water in agricultural activities has become frequent (LIRA et al, 2015;MUNNS;GILLIHAM, 2015;RODRIGUES et al, 2018).…”
Section: Introductionmentioning
confidence: 99%